2015
DOI: 10.3171/2014.12.jns141777
|View full text |Cite
|
Sign up to set email alerts
|

Neuroophthalmological outcomes associated with use of the Pipeline Embolization Device: analysis of the PUFS trial results

Abstract: . disclosure Dr. Becske is a consultant/proctor in the use of the Pipeline Embolization Device for Covidien. Dr. Saatci's institution received fees for participation in review activities from Chestnut Medical, and she received consultancy fees from ev3/Covidien. Dr. McDougall received consultancy fees from the Covidien Medical Advisory Board. Dr. Szikora and his institution received consulting fees or honoraria from Chestnut Medical, and he received consultancy fees from Stryker Neurovascular and ev3/ Covidien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
47
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(48 citation statements)
references
References 17 publications
1
47
0
Order By: Relevance
“…In addition, Briganti et al 30) reported that the mortality after flow diverter treatment of lesions at the same site was 4%. While simple comparison of these results is not approved, they suggest Table 2 Comparison of the patient characteristics, complication rate, and retreatment rate among the 4 papers and our study : minimum-maximum; DAE: disobliteration after embolization of ruptured aneurysm; ME: Mass effect; SAH: subarachnoid hemorrhage patients with CNP was 64% after treatment using Pipeline, 33) and it tended to be higher in those treated using Pipeline. The number of patients treated at our hospital is small, and generalization of the results is not warranted, but they suggest the possibility that aneurysms in the Bouthillier C4 and C5 segments without CNP can be treated with a low complication rate and a relatively low retreatment rate by the current coil embolization procedure.…”
Section: Discussionmentioning
confidence: 67%
“…In addition, Briganti et al 30) reported that the mortality after flow diverter treatment of lesions at the same site was 4%. While simple comparison of these results is not approved, they suggest Table 2 Comparison of the patient characteristics, complication rate, and retreatment rate among the 4 papers and our study : minimum-maximum; DAE: disobliteration after embolization of ruptured aneurysm; ME: Mass effect; SAH: subarachnoid hemorrhage patients with CNP was 64% after treatment using Pipeline, 33) and it tended to be higher in those treated using Pipeline. The number of patients treated at our hospital is small, and generalization of the results is not warranted, but they suggest the possibility that aneurysms in the Bouthillier C4 and C5 segments without CNP can be treated with a low complication rate and a relatively low retreatment rate by the current coil embolization procedure.…”
Section: Discussionmentioning
confidence: 67%
“…31 Most recently, Sahlein et al performed a sec ondary analysis of the Pipeline for Uncoilable or Failed Aneurysms trial and found that 40% of 98 patients with paraclinoid aneurysms had preoperative visual impair ment; however, this analysis only considered large and gi ant aneurysms. 46 The heterogeneity of the data reported in the literature demonstrates that there is no conclusive estimate for the rate of visual symptoms among patients with paraclinoid aneurysms. This metaanalysis of 39 studies with a total of 2458 patients found that 38% of pa tients with paraclinoid aneurysms presented with visual impairment across a range of aneurysm sizes, geographic regions, and referral patterns.…”
Section: Discussionmentioning
confidence: 84%
“…11,31,46 The mechanism of visual impairment is not well understood, but may result from direct mass effect of the aneurysm sac com pressing the optic nerve, inflammation, or retinal artery thrombosis. 1,18,24,28,46,49 In addition to presenting with visual symptoms, patients with intact baseline vision can develop iatrogenic visual deficits following treatment by many of these same mechanisms.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…21) In addition, optic neuropathy may develop from direct compression by large and giant aneurysms, resulting in VA and VF deficits. 21) The Pipeline for Uncoilable or Failed Aneurysms (PUFS) trial 21) observed a neuro-ophthalmological baseline deficit in 39 of 98 patients (39.8%) that was presumed attributable to the intracranial aneurysm, with a higher proportion of patients having aneurysms of the cavernous segment (57%) than of the petrous (0%), superior hypophyseal (22%), paraophthalmic (27%), or supraclinoid (25%) segments.…”
Section: Discussionmentioning
confidence: 99%